A newly developed glucagon sandwich ELISA is useful for more accurate glucagon evaluation than the currently used sandwich ELISA in subjects with elevated plasma proglucagon‐derived peptide levels - Kobayashi, Masaki; Maruyama, Nobuhiro; Yamamoto, Yukako; Togawa, Takeshi; Ida, Takanori; Yoshida, Morikatsu; Miyazato, Mikiya; Kitada, Masahisa; Hayashi, Yoshitaka; Kashiwagi, Atsunori; Kitamura, Tadahiro (Journal of diabetes investigation, 2023)
Aims/Introduction Glucagon, a peptide hormone produced from proglucagon, is involved in the pathophysiology of diabetes. Plasma glucagon levels are currently measured by sandwich enzyme‐linked immunosorbent assay (ELISA), but the currently used sandwich ELISA cross‐reacts with proglucagon‐derived peptides, thereby providing incorrect results in subjects with elevated plasma proglucagon‐derived peptide levels. We aimed to develop a more broadly reliable ELISA for measuring plasma glucagon levels. Materials and Methods A new sandwich ELISA was developed using newly generated monoclonal antibodies against glucagon. After its validation, plasma glucagon levels were measured with the new ELISA and the currently used ELISA in subjects who underwent laparoscopic sleeve gastrectomy (LSG) and in outpatients with suspected glucose intolerance. The ELISA results were compared with those from liquid chromatography‐high resolution mass (LC‐HRMS) analysis, which we previously established as the most accurate measuring system. Results The new ELISA has high specificity (<1% cross‐reactivities) and high sensitivity (a lower range of 0.31 pmol/L). Plasma glucagon values in the subjects who underwent laparoscopic sleeve gastrectomy and some outpatients with suspected glucose intolerance differed between the new ELISA and the currently used ELISA. These subjects also showed markedly high plasma glicentin levels. Despite the elevated plasma glicentin levels, the new ELISA showed better positive correlation with LC‐HRMS than did the currently used ELISA. Conclusions The new ELISA enables more accurate measurement of plasma glucagon than the currently used ELISA, even in subjects with elevated proglucagon‐derived peptide levels. It should be clinically useful in elucidating the pathophysiology of individual diabetic patients. A new glucagon sandwich enzyme‐linked immunosorbent assay (ELISA) has been developed that enables highly reliable measurement. The new ELISA provided much more reliable glucagon values than the currently used ELISA even in the subjects with elevated plasma proglucagon‐derived peptide levels. This new ELISA should be clinically useful in elucidating the pathophysiology of individual diabetic patients.